Worldwide Satellite Imagery presented on CD-ROM Toposar (tm) Dem Sample Papua, New Guinea created by Intermap (Canada Radarsat International)
Derived from Radarsat stereo image, Samples area in Western Papua, New Guenia, 16kmx15km, X,Y,Z coordinates in 50 metre UTM Grid
Title on booklet cover
Keywords: Image Satellites -- Papua, New Guenia